Phase imaging of nanostructures. (19th September 2008) - Allman, Brendan; Ishizuka, Kazuo; Nugent, Keith
Two properties of a wave, its intensity and colour, are familiar to all of us. A third property, phase, is less familiar and carries shape information. Quantitative Phase Imaging (QPI), the method discussed in this paper, measures phase information. It utilises the fact that a phase distribution in one plane effects the intensity distribution after propagation. Many samples at the nanoscale are phase objects. For nanostructures, the phase change of the incident wave is strong, while the modulation of amplitude may be negligible. QPI generates the refractive and thickness structure of these transparent samples in a transmission imaging geometry.